CLIMATE CHANGE ADAPTATION IN RURAL DEVELOPMENT IN LATVIA:AN IMPACT ASSESSMENT - Paredne, Inguna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
This paper is based on empirical research and an analysis of individual cases of opportunities, which are provided or limited by climate adaptation in rural development in Latvia. The empirical research focuses on adaptation to climate changes, based on previous studies, scientific knowledge and approved theories of climate change adaptation in sector policies and updates of them in Latvia. The research includes an analysis of policy documentation on integration of targets and principles of climate change adaptation in the context of environmental policy and environmental management, focusing on the importance of use of farming and the environmental sector’s environmental communication means in the reduction of the sector’s vulnerability caused by climate changes. The pilot projects carried out in Latvia under sectoral policies comprise an essential part of the bibliographical analysis. Various views of main parties involved are summarized using the approach of attitude, action and investment. Different views and attitudes acess to information exist, as well as on the need for parties to get involved in climate change reduction. The purpose of the research is to assess impact of climate change adaption on development of rural areas in Latvia.